-3x+1=11

Simple and best practice solution for -3x+1=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x+1=11 equation:


Simplifying
-3x + 1 = 11

Reorder the terms:
1 + -3x = 11

Solving
1 + -3x = 11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + -3x = 11 + -1

Combine like terms: 1 + -1 = 0
0 + -3x = 11 + -1
-3x = 11 + -1

Combine like terms: 11 + -1 = 10
-3x = 10

Divide each side by '-3'.
x = -3.333333333

Simplifying
x = -3.333333333

See similar equations:

| 6x-3=9x+12 | | 3x+6x-18=18-17x | | e^5x+4=6e^3x | | x*x+32*32=20*20 | | -4x+8y=10 | | 2[3(x+2)-x]=4 | | 3(4x+1)=-117 | | 6X-8Y=-12 | | x*x+16*16=17*17 | | 4x-1/x^2-3=0 | | 2/7y+5=-9 | | x^2+7x-144=0 | | 72=9-18x | | (2x-2)/3=-8 | | 3=y/4.8 | | -6.5x+5=-11+1.5x | | (y-13)=0.5(8x-14) | | f(15)= | | 2x+30+14x+30+4x+60=180 | | 42*42+40*40=x*x | | 88=4v+8 | | 56*56+33*33=x*x | | 9-12=3n | | 9m+5n-5m+8n= | | 12x-9y+3= | | 2x-x^3+5=3 | | 0.3x+0.2(x-7)=8 | | 6x-3=9# | | 2X-6Y=2 | | 9y=x | | 0.5x^4+1=1.25x^3-1 | | 9x+25=4x |

Equations solver categories